2018
DOI: 10.1002/ptr.6161
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin protects against liver ischemia/reperfusion injury in mice via inhibiting HMGB1‐TLR4 signaling pathway

Abstract: Hepatic ischemia/reperfusion (I/R) injury is a major cause of high morbidity and mortality after liver resection, transplantation, and hemorrhagic shock. Paeoniflorin (PF), the main substance of glucosides in Radix Paeoniae Alba, has been widely used to treat various hepatic inflammatory diseases including I/R injury. However, the underlying mechanisms of PF on hepatic I/R injury remain further investigated. In this study, the liver I/R model was performed by clamping the portal vein and hepatic artery with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 28 publications
(35 reference statements)
2
30
0
Order By: Relevance
“…8 a-c). Effects of SSB extract on HMGB1, TRAF6, TLR4, IκB, p-IκBα, and NF-κB65 protein expression in LPS/D-GalN-induced acute liver injury in mice HMGB1/TLR4/NF-κB65 is a crucial inflammatory pathway that may be involved in LPS/D-GalN-induced acute liver injury [31]. We explored the effects of SSB extract on HMGB1, TRAF6, TLR4, IκB, p-IκB-α, and NF-κB65 protein expression in LPS/D-GalN-induced acute liver injury in mice.…”
Section: Effects Of Ssb Extract On Mir-124 Expression Level In Lps/ Dmentioning
confidence: 99%
“…8 a-c). Effects of SSB extract on HMGB1, TRAF6, TLR4, IκB, p-IκBα, and NF-κB65 protein expression in LPS/D-GalN-induced acute liver injury in mice HMGB1/TLR4/NF-κB65 is a crucial inflammatory pathway that may be involved in LPS/D-GalN-induced acute liver injury [31]. We explored the effects of SSB extract on HMGB1, TRAF6, TLR4, IκB, p-IκB-α, and NF-κB65 protein expression in LPS/D-GalN-induced acute liver injury in mice.…”
Section: Effects Of Ssb Extract On Mir-124 Expression Level In Lps/ Dmentioning
confidence: 99%
“…Therefore, a reduction in the innate immune response might contribute to this process. This research finally found that inhibiting the HMGB1-TLR4 signaling pathway is the crucial mechanism of paeoniflorin in hepatic I/R injury (Xie et al, 2018). Another study also supported this conclusion.…”
Section: Hepatic Ischemia/reperfusion Alleviationsupporting
confidence: 62%
“…Experiments have shown that paeoniflorin can inhibit ischemia/reperfusion (I/R)-induced hepatocyte apoptosis and cysteinyl aspartate specific proteinase 3 (caspase-3) activation, as well as dampening I/R-induced neutrophil infiltration and pro-inflammatory cytokine production. The protective effect on the liver is associated with the inhibition of the I/R-activated high mobility group box-1 (HMGB1)-toll-like receptors 4 (TLR4) signaling pathway to attenuate hepatic inflammatory response (Xie et al, 2018). In the CCl4-induced acute liver injury model, RPR water extracts protect the liver from CCl4-induced oxidative damage in rats, which was associated with antioxidant and free radical scavenging activity (Li et al, 2011;Wang et al, 2012).…”
Section: The Pharmacological Actions Of Rpr and Rpamentioning
confidence: 99%